PENGARUH KOMPETENSI DOSEN DAN KUALITAS PELAYANAN TERHADAP MOTIVASI BERPRESTASI MAHASISWA - Karsadi, Ardi (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2002)
The increasingly admission trend  of new students in the school of communication science of the University of Dr. Moestopo (Religious) serious attention, especially for the quality services of learning process provided to the enrolled students. The hypothesis of this study was a positive relationship betweenboth the instructors competence and  the schools service quality togetherwith the students achievement motivation seems   to occur. The study results show that  a positive   correlation between   instructors competence and students achievement motivation exists significantly with a correlation levelof0.228. Moreover, it is proved that a positive correlation be tween  schools   quality   service   and students  achievement  motivation occurs significantly with a correlation level of 0,228.  Moreover it is proved that a positive correlation between schools quality  service, together, and students achievement motivation with a correlation level of 0.264. The study also  suggeststhat correlation contributions are 5.2 %; 5.5 %; and 7.0 %.   Although the contributions are not so big, the test re sults  show that  they  are  significant enougl.